2016
DOI: 10.1024/0301-1526/a000495
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous mechanical thrombectomy in the treatment of acute and subacute occlusions of the peripheral arteries and bypasses

Abstract: Summary:Background: The aim of this prospective single-centre study was to analyse the immediate results, failures and complications of percutaneous mechanical thrombectomy using the Rotarex catheter in the treatment of acute and subacute occlusions of peripheral arteries and bypasses, as well as to evaluate long-term outcomes of this method. Patients and methods: Patients with acute (duration of symptoms < 14 days) or subacute (duration of symptoms > 14 days and < 3 months) occlusions of peripheral arteries a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 14 publications
4
23
1
Order By: Relevance
“…5, [14][15][16][16][17][18][19] When comparing our results to those reported by Wissgott et al, 21 who retrospectively studied 265 patients who underwent RT with Rotarex, we found similar results regarding technical success, amputation, and embolization rates.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…5, [14][15][16][16][17][18][19] When comparing our results to those reported by Wissgott et al, 21 who retrospectively studied 265 patients who underwent RT with Rotarex, we found similar results regarding technical success, amputation, and embolization rates.…”
Section: Discussionsupporting
confidence: 92%
“…In the majority of patients (59.2%, n ¼ 334) undergoing PMT procedures during this period, the smaller Rotarex System (6F) was used. The mean lesion length was 159 mm (range 2-27.8 cm), with SFA(n ¼ 346;58.3%) and Pop (n ¼ 114; 19.2%) vessel segments as the mostly treated; 127 (21.4%) had undergone a prior PTA. Moderate and severe calcification was present in 121 (23.3%) of the lesions.…”
Section: Resultsmentioning
confidence: 99%
“…153 One study reported that re-thrombosis was more frequent after Rotarex was used for bypass graft thrombosis, longer arterial occlusions, and in the presence of poor runoff. 154 3.6.3. Ultrasound accelerated thrombolysis.…”
Section: Iiamentioning
confidence: 99%
“…This issue of Vasa -European Journal of Vascular Medicine contains a prospective analysis by Stanek et al [13], who provide further evidence of the benefi ts of a pure mechanical thrombectomy approach in an indiff erent patient cohort with acute and subacute limb ischemia due to a variety of causes. A commendable feature is their inclusion of patients with a wide range of clinical symptoms (categories I -III of acute occlusions) and angiographic fi ndings (native infra-inguinal arteries, bypasses), both of which are encountered frequently in daily routine.…”
mentioning
confidence: 99%